Nathan Carmody: capstone - Carmody, Nathan, artist (Colorado State University. Libraries, 2026)
The artist's statement: Much of my work during my time in undergrad has been focused in the realm of printmaking, with a specific focus on experimental intaglio, cyanotype, and lithography techniques. More recently, these mediums have aided explorations in book arts. As an artist, I find myself considering my body quite frequently, especially working in mediums that are dominated by process. In printmaking, the creation of an edition is as much about the procedure as it is the resulting work. The physical component to this creative process informs the way I think about my relationship with labor and repetition. I am able to begin questioning how the gestures, impression, and rhythm of my body become embedded in each mark. In printmaking, I find myself enjoying the laborious tasks the most. These repetitive moments become a meditation. What I am beginning to understand, is that I enjoy existing in the middle of something. I enjoy the physical matter of the process, and find peace in moving through a medium. Through printmaking, I'm able to unpack how I take up and move through space as a someone whose identity exists outside of normative expectations of gender and sexuality. I am able to evaluate what it means to exist as a body in process.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: printmaking